Changes of clinical symptoms in patients with new psychoactive substance (NPS)‐related disorders from fiscal year 2012 to 2014: A study in hospitals specializing in the treatment of addiction. Issue 2 (9th April 2019) - Funada, Daisuke; Matsumoto, Toshihiko; Tanibuchi, Yuko; Kawasoe, Yasunari; Sakakibara, Satoru; Naruse, Nobuya; Ikeda, Shunichiro; Sunami, Takashi; Muto, Takeo; Cho, Tetsuji
Abstract: Aims: The use of new psychoactive substances (NPS) has become increasingly widespread over the last decade, in Japan and internationally. NPS are associated with a range of increasingly serious clinical, public, and social issues. Political measures to ameliorate the effects of NPS in Japan have focused on tightening regulation rather than establishing treatment methods. The current study sought to compare the neuropsychiatric symptoms of patients with NPS‐related disorders across several years. We examined patients who attended specialized hospitals for treating addiction, to elucidate the impacts of legal measures to control NPS. Methods: Subjects (n = 864) were patients with NPS‐related disorders who received medical treatment at eight specialized hospitals for treating addiction in Japan between April 2012 and March 2015. Clinical information was collected retrospectively from medical records. Results: Among psychiatric symptoms, the ratio of hallucinations/delusions decreased over time across 3 years of study (first year vs second year vs third year: 40.1% vs 30.9% vs 31.7%, P  = 0.037). Among neurological symptoms, the ratio of coma/syncope increased over the 3‐year period (7.8% vs 11.0% vs 17.0%, P  = 0.002), as did the ratio of convulsions (2.8% vs 4.3% vs 9.7%, P  = 0.001). Conclusion: The symptoms associated with NPS were primarily psychiatric in the first year, while the prevalence of neurological symptoms increased each year. The risk of death and the severity of symptoms were greater in the third year compared with the first year, as regulation of NPS increased. Abstract : We collected information retrospectively based on medical records and compared with psychiatric and neurological symptoms of NPS users observed in the fiscal year of their first medical examination. We found that adverse health effects resulting from the use of NPS were changed from mainly psychiatric symptoms to neurological symptoms. These findings suggest the possibility that contained more dangerous and toxic compounds after drug‐related regulations had been tightened.